MATHEMATICAL MODELS OF INFORMATION PROCESSING AND MANAGEMENT SYSTEMS - Zh.E. Kenzhebayeva (Academic Journal of Physical and Chemical Sciences, 2019)
The modern scientific and technical revolution is accompanied by the rapid penetration of digital and computer equipment into technical systems for various purposes, which opens up prospects for the implementation of increasingly complex and efficient information processing and control algorithms. This led to an increase in interest in the theory of linear non-stationary systems (LNS), which, firstly, provides models of modern complex control objects and information transfer channels, and, secondly, is the theoretical basis for the synthesis of non-stationary systems with significantly richer potential than stationary systems. A similar situation is observed simultaneously in various fields of theory and technology, including automatic control, the theory of information processing systems, radio engineering, the theory of pattern recognition, etc.